2012
DOI: 10.1016/j.yqres.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Absolute geomagnetic intensity determinations on Formative potsherds (1400–700 BC) from the Oaxaca Valley, Southwestern Mexico

Abstract: New Thellier-Coe archeointensity determinations have been measured on 15 potsherds from the Oaxaca Valley belonging to three of the four Formative Periods (Pre-Classical) of Mesoamerica, spanning 1400–700 BC. Seven of these are considered to be reliable and indicate a geomagnetic field strength of about 30 μT. This value is some 75% of the present geomagnetic field strength but is in agreement with the absolute intensities predicted from global models for this time and location, and consistent with coeval publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…As already suggested by Pétronille et al . [], the main tendencies, given by both the few available archeointensity data from Central and South Mesoamerica and the model predictions, are anticorrelated with the main tendencies given by oxygen isotope record from Lake Punta Laguna.…”
Section: Main Results and Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…As already suggested by Pétronille et al . [], the main tendencies, given by both the few available archeointensity data from Central and South Mesoamerica and the model predictions, are anticorrelated with the main tendencies given by oxygen isotope record from Lake Punta Laguna.…”
Section: Main Results and Discussionmentioning
confidence: 65%
“…(a) Currently available absolute intensity data from Mesoamerica (relocated to Arraro) derived from archeological artifacts and historic lava flows (This study and Pétronille et al ., ). Also shown are the data derived from model prediction from CALS3K.4 for the past 3 ka (Korte and Constable, ) and CALS10K.1b for the past 10 ka [ Korte et al ., ].…”
Section: Main Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In Mexico, a large number of archaeomagnetic studies on baked clays or lava flows have been published in the last 10 years (e.g., Fanjat et al, 2013;Mahgoub et al, 2017;Mahgoub et al, 2019bMahgoub et al, , 2019aMahgoub et al, 2019aMahgoub et al, , 2019bPétronille et al, 2012;Rodriguez-Ceja et al, 2009;Rodriguez-Trejo et al, 2019;Terán et al, 2016), but a recent critical analysis of the Mexican dataset showed that around 70% of these data cannot be considered as high quality, according to basic selection criteria. Two local secular variation curves have been recently proposed using only Mexican data (Mahgoub et al, 2019a) or also some from the southwestern United States (Goguitchaichvili et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a long tradition of archeomagnetic studies in Northern and Central America, with the first studies in the mid 60s (e.g., Bucha et al, 1970;Lee, 1975 for Mexico and see Jones et al, 2021 for USA) and continuous improvements since (e.g., Alva-Valdivia et al, 2020Dubois, 1989;Hagstrum & Champion, 2002;Hervé, Perrin, Alva-Valdivia, Tchibinda Madingou, et al, 2019;Jones et al, 2020Jones et al, , 2021Lengyel & Eighmy, 2002;Mahgoub, Juárez-Arriaga, Böhnel, Manzanilla, & Cyphers, 2019;Morales et al, 2009;Pétronille et al, 2012;Rodríguez-Trejo et al, 2019;Schaafsma et al, 2002;Soler-Arechalde et al, 2019;Sternberg, 1989;Wolfman, 1990). For the past 2 kyrs, around 325 intensities and 690 directions, respectively 11% and 12% of the worldwide archeomagnetic data set (GEOMAGIA50.v3.4; Brown et al, 2021), have been published.…”
mentioning
confidence: 99%